2019
DOI: 10.1186/s12889-019-7142-1
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of youths as change agents on cardiovascular disease risk factors among adult neighbours: a cluster randomised controlled trial in Sri Lanka

Abstract: Background Mobilising non-professional health workers has been successful in improving community health, but the effectiveness of an education program targeting youths in a community-based approach remains unclear. The objective of this study was to investigate the effect of an intervention with youth on cardiovascular disease risk factors of community adults. Methods A 12-month cluster randomised trial was conducted in a semi-urban area of Colombo in Sri Lanka. Facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…The present study also observed that middle women aged (between 30 and 40 years) have relatively higher BMI than younger women. Thus, the community-level promotion of healthy lifestyles behaviours, especially among women aged in their 30's, could help to halt the rise of the overnutrition and obesity (43,44) .…”
Section: Discussionmentioning
confidence: 99%
“…The present study also observed that middle women aged (between 30 and 40 years) have relatively higher BMI than younger women. Thus, the community-level promotion of healthy lifestyles behaviours, especially among women aged in their 30's, could help to halt the rise of the overnutrition and obesity (43,44) .…”
Section: Discussionmentioning
confidence: 99%
“…Data for the present study were derived from a cluster randomized controlled trial that examined the effect of health-promoting activities by trained youth club members on CVD risk among community adults in a semi-urban area of Colombo, Sri Lanka [20]. To recruit study participants, we randomly selected 24 Grama Niladari (GN) divisions, i.e., the rural level administrative division in the country [21].…”
Section: Study Proceduresmentioning
confidence: 99%
“…We defined non-smokers as the low-risk group, including never and former smokers, and the high-risk group as current smokers [24]. The low-risk group for alcohol consumption was defined as �2 drinks/day for men and �1 drink/day for women based on the Dietary Guidelines in the United States [25], which was also referred in the above-mentioned intervention study in Sri Lanka [20]. Food-based dietary guidelines for Sri Lankans recommend consuming 2-3 servings/day of fruits and 3-5 servings/day of vegetables [26].…”
Section: Construction Of the Healthy Lifestyle Indexmentioning
confidence: 99%
“…One study was conducted in Kenya in sub-Saharan Africa [ 32 ] and another in three countries, China, India and Mexico [ 55 ]. Of the remaining studies, seven were from India [ 33 37 , 43 , 55 ], five from China [ 46 50 ], and two from Iran [ 26 , 30 ], Pakistan [ 38 , 39 ] and Sri Lanka [ 42 , 44 ]. Bangladesh [ 40 ], Grenada [ 54 ], Malaysia [ 51 ], Nepal [ 56 ], Thailand [ 53 ], Russia [ 52 ] and Vietnam [ 41 ] each had a single study.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were cluster randomized controlled trials [ 33 , 34 , 39 , 40 , 42 45 , 56 ], eight were randomized controlled trials [ 35 37 , 46 , 48 , 50 , 53 , 54 ] and ten were controlled before and after studies [ 26 , 30 , 32 , 38 , 41 , 47 , 49 , 51 , 52 , 55 ]. Studies were carried out in different contexts; eight in urban [ 30 , 32 , 36 , 37 , 39 , 48 , 50 , 56 ], three in semi-urban [ 42 , 44 , 51 ], eight in rural [ 33 , 35 , 40 , 41 , 43 , 45 , 49 , 53 ] and two in both rural and urban areas [ 26 , 38 ]. In six studies, the context was unclear [ 34 , 46 , 47 , 52 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%